Prevalence, risk, and outcomes of venous thromboembolic events in kidney transplant recipients: a nested case-control study. Issue 1 (31st December 2023) - Bhargava, Vinant; Meena, Priti; Bhalla, Anil Kumar; Rana, Devinder Singh; Gupta, Ashwani; Malik, Manish; Gupta, Anurag; Tiwari, Vaibhav
Abstract: Introduction: Thromboembolism is more common in kidney transplant recipients (KTRs) than in the general population. Studies evaluating arterial and venous thromboembolism (VTE) in KTRs are scarce and the magnitude and risk factors are mostly undefined. Methods: A nested control study was conducted from January 1, 2007, to December 31, 2019. Adult KTRs who were detected to have VTE events during this period were included. The primary outcome was to assess the prevalence of VTE in this population. Secondary outcomes were the assessment of the time to occurrence of the thromboembolic events after transplantation and assessing the risk factors and patient survival. For each subject studied, 4 controls were matched from the data set. Results: Amongst 2158 patients, 97 (4.5%) were found to have VTE. The median follow-up time was 3.9 years (6–156 months). A total of 101 VTE events were recorded. The most common site of VTE was the lower limb deep vein thrombosis in 79 patients (0.03%)).In multivariate Cox regression analysis, serum creatinine of more than 3 mg/dl [HR 1.30, 95% CI (1.03–1.38)] was independently associated with increased VTE risk. Patients who developed a VTE had higher mortality as compared to patients who did not develop VTE. No increased risk of graft failure was found in VTE patients. Conclusion: This study suggests that kidney transplantation surgery is a moderate risk factor for VTE, and VTE is associated with higher morbidity and mortality. However, prospective studies are needed to establish a definite role of VTE in outcomes in KTRs.